Analisis Efisiensi di Bank Victoria Syariah dengan Pendekatan Principal Component Analysis – Data Envelopment Analysis - Asyilla Audria Putri; Rendra Erdkhadifa (Jurnal Ilmiah Ekonomi Islam, 2023)
ABSTRACT This research is motivated by the role of Islamic banking in the welfare of society by improving the quality of services provided. The quality of bank services can be measured through service efficiency at bank. This efficiency is a balance between those served and those serving, hereinafter referred to as input and output. In this study, we wanted to know the level of efficiency of Bank Victoria Syariah using the Principal Component Analysis-Data Envelopment Analysis (PCA-DEA) method. The models used are PCA-CCR and DEA-CCR. The input data used are profit sharing ratios, labor costs, total assets, third party funds and fixed assets while the output data used are main operating income, other operating income, buying and selling principle financing, profit sharing financing principles and current assets. From the various PCA-DEA models used, different efficiency values are generated for the same financial statements and there is only one financial report that has a fixed efficiency value among other financial reports, namely the January 2021 financial report. Keyword: Efficiency, DEA-CCR, Islamic Banking, PCA-CCR